Faith in the Digital Age: Narrative Accounts of Madrasah Teachers Navigating Islamic Education in the 4.0 Industrial Revolution - Zaenol Fajri; Khofidhah Dwi Sholehah; Muhammad Naim Fakhirin Rezani (International Journal of Educational Narratives, 2026)
Background. The rapid digital transformation in the Industrial Revolution 4.0 requires Islamic Religious Education (IRE) to adopt innovative approaches to improve learning quality and student achievement. However, prior studies predominantly focus on general digitalization or higher education contexts, with limited empirical evidence on context-specific strategies at the elementary madrasah level. This study addresses this gap by offering a contextual and practice-based analysis of IRE digitalization. Purpose. This study aims to analyze digitalization strategies in improving learning quality and student achievement at MI Al-Islamiyah, including implementation processes, supporting and inhibiting factors, and their educational impact. Method. This study employed a qualitative case study design to obtain in-depth and contextual insights. Participants—including the principal, deputy head of curriculum, IRE teachers, operators, and parents—were purposively selected for their direct involvement in the implementation of digital learning to ensure data relevance and credibility. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model. Data validity was strengthened through triangulation, member checking, and audit trails. Results. The findings reveal that digitalization is systematically implemented through institutional policies, teacher capacity building, and integrated digital systems. The use of interactive media, RDM-based assessment, and digital administration increases student participation, motivation, and learning interaction, while enhancing transparency and organization of assessment. Evidence shows more active engagement and structured learning processes, although improvements in academic achievement remain gradual due to infrastructure and competency constraints. Conclusion. Digitalization serves as a strategic catalyst for improving learning quality, thereby mediating student achievement. This study contributes theoretically by proposing a contextual model of IRE digitalization at the elementary madrasah level and practically by guiding sustainable implementation through institutional support, continuous teacher training, and adaptive strategies in Islamic education.